Measurement and clinical implications of choroidal thickness in patients with inflammatory bowel disease - Onal,Ibrahim Koral (2015)
ABSTRACTPurpose:Ocular inflammation is a frequent extraintestinal manifestation of inflammatory bowel disease (IBD) and may parallel disease activity. In this study, we evaluated the utility of a choroidal thickness measurement in assessing IBD activity.Methods:A total of 62 eyes of 31 patients with IBD [Crohn's disease (CD), n=10 and ulcerative colitis (UC), n=21] and 104 eyes of 52 healthy blood donors were included in this study. Choroidal thickness was measured using enhanced depth imaging optical coherence tomography. The Crohn's disease activity index (CDAI) and the modified Truelove Witts score were used to assess disease activity in CD and UC, respectively.Results:No significant differences in mean subfoveal, nasal 3000 μm, or temporal 3000 μm choroidal thickness measurements (P>0.05 for all) were observed between IBD patients and healthy controls. Age, smoking, CD site of involvement (ileal and ileocolonic involvement), CDAI, CD activity, and UC endoscopic activity index were all found to be significantly correlated with choroidal thickness by univariate analysis (P<0.05). Smoking (P<0.05) and the CD site of involvement (P<0.01) were the only independent parameters associated with increased choroidal thickness at all measurement locations.Conclusions:Choroidal thickness is not a useful marker of disease activity in patients with IBD but may be an indicator of ileal involvement in patients with CD.